The Inhibitory G Protein Gi Identified as Pertussis Toxin-Catalyzed ADP-Ribosylation - Toshiaki Katada (2012)
Pertussis toxin (PTX) produced by Bordetella pertussis was first introduced by Ui and his colleagues in research on signal transduction under the name islet-activating protein in 1979, when the mechanism of toxin-induced stimulation of insulin release from pancreatic islets was reported in the rat. The stimulatory effect of PTX in vivo results from the blockage of α2-adrenergic receptor-mediated inhibition of insulin release. The receptor-induced inhibition of cAMP formation was also abolished in pancreatic islets isolated from PTX-treated rats, suggesting that the toxin caused uncoupling of adenylyl cyclase inhibition from receptor stimulation. The action of PTX on isolated membranes required a cytosolic factor, nicotinamide adenine dinucleotide (NAD), and the uncoupling induced by PTX was shown to be due to the toxin-catalyzed ADP-ribosylation of a 41-kDa protein with NAD as another substrate. The 41-kDa PTX substrate was soon identified and purified as the α-subunit of the inhibitory G protein that transmits an inhibitory signal from membrane receptors to adenylyl cyclase. After demonstration of the molecular mechanism of PTX, the toxin was widely utilized as a probe for identifying and analyzing major αβγ-trimeric G proteins. Thus, PTX-sensitive G proteins appeared to carry positive and negative signals from many membrane receptors to a variety of effectors other than adenylyl cyclase.